Clean and Healthy Behavior Education Vuttisat Vittayanuson Students Krabi Thailand (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Community service activities carried out by STKIP Muhammadiyah Kuningan present knowledge sharing through programs for the community in the Vuttisat Vittayanuson School environment, Koh Lanta Noi, Krabi Thailand. The purpose of this service activity is to carry out the PHBS program based on the results of the analysis and goals of KKN students. The method of community service activities uses focus group discussions (FGD) both internally as a Community Service Team (PKM) and with residents of the Vuttisat Vittayanuson School. The results of the service activities from the program that have been implemented consist of working together to clean the school environment, exercise together, wash hands regularly and how to maintain personal hygiene.